The Female Character Struggle to Obtain Equality in Beauty and the Beast - Muafiah, Rahmawati; Suryani, Suci (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
In the patriarchy system, women have restriction in delivering thoughts and action, accessing education, and obtaining rights. However, they struggle hard to attain equality in those aspects in their life. Hence, the study aims to find out the restriction experienced by women character named Belle and how she fight against the restriction to obtain her freedom and independence as women. While the original "Beauty and the Beast" story has roots in classic fairy tales, modern adaptations, such as the one by Elizabeth Rudnick, transform it into a contemporary literary work. This book, applying the theory of Liberal Feminism, can be seen as a form of challenge or movement within the postmodern era. Using the theory of liberal feminism espoused by Rosemarie Tong (1980) those two issues will be analyzed through reading book entitle “Beauty and the Beast” by Elizabeth Rudnick’s (2017). The library use in this study is to help the writer to analyze the data regarding to the issues in the novel.